The archaeology of chimpanzee technology: ecological perspectives on strategies of early hominin raw material acquisition and the formation of technological landscapes - Almeida Warren, K (2022)
Since the discovery of the first Oldowan tools, the study of Plio-Pleistocene (~3.5 – 0.8 million-years ago) lithic assemblages has played an important part in discerning early hominin behaviour. However, despite the subsequent 80 years of research, the most fundamental questions of human evolution remain unanswered: What were the behavioural predecessors of stone tool use? How did our earliest technological ancestors live? And how did tool use, and the lithic assemblages produced, fit into the wider behavioural and ecological landscape? Using a primate archaeology approach, this thesis seeks to expand our understanding of how the environment may have shaped hominin behaviour by focusing on two main areas of enquiry: perishable technology and landscape use. It also aims to tackle some of the methodological challenges surrounding cross-comparison between hominin and chimpanzee archaeological records, such as the discrepancy in resolution and accuracy of spatial data collection methods. Chapter 1 provides an introduction and an overview of the historical backdrop and methodological developments to the entire thesis. Chapter 2 discusses the development of a new spatial mapping method which enables, for the first time, standardised spatial resolution across the primate order. This is followed by three core empirical chapters. Chapter 3 explores the archaeology of perishable technology by investigating the diversity and drivers of plant material procurement strategies in chimpanzee termite-fishing. The results indicate that some differences between the three study sites could be attributed to ecological differences, while others suggested that cultural processes were at play. These findings reveal techno-cultural variation and flexible exploitation strategies that parallel the behaviours associated to the use of stone tools by our earliest ancestors, suggesting these behaviours have a much deeper origin than originally thought. Chapters 4 and 5 combine landscape archaeology with agent-based modelling to produce the first landscape-scale study of the ecological and behavioural correlates of chimpanzee stone tool-use. Analyses of the empirical data in Chapter 4 uncovered spatial relationships between nut-cracking sites, proximity to nest sites, and food availability, suggesting the presence of activity hotspots reminiscent of patterns of landscape-use that have been proposed for our earliest tool-using ancestors. Following from this, agent-based modelling results presented in Chapter 5 indicate that variations in the spatial distribution of resources did not produce variations in the spatial patterning of nut-cracking activity. This suggests that the dynamic relationship between the environment, behaviour and the spatial patterning of stone tool use may be even more complex than originally thought. Finally, Chapter 6 reports on the current conservation status of and major threats to the Diécké Forest — the second largest forest in Guinea and home to another population of nut-cracking chimpanzees. It was found that the chimpanzee presence in the area continues to decline with no recent evidence of nutcracking or other activities. Together with research conducted in Bossou, this research provides important insights into the fragility of West African chimpanzee populations and their cultural heritage.